Competing with data quality : concepts, tools, and techniques for building a successful approach to data quality - Jugulum, Rajesh (Hoboken, New Jersey : Wiley, 2014)
'Competing with Data Quality provides a road map for corporations to improve data quality and meet Dodd-Frank, BASEL III, Solvency II, and other pervasive regulatory oversight programs. This book outlines a holistic data quality (DQ) approach that businesses can adopt to energize their DQ innovation processes, perfect their data gathering and usage practices, and ensure robust and reliable data is available to make judicious decisions. It also addresses the end-to-end DQ deployment process: Define, Assess, Improve and Control. Numerous cases and'lessons learned' facilitate understanding'--
'This book aims at outlining a holistic data quality (DQ) approach that businesses can adopt to energize their DQ innovation processes, perfect their data gathering and usage practices and ensure robust and reliable data is available to make judicious decisions'--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Electronic data processing -- Quality control; Management; BUSINESS & ECONOMICS -- Quality Control; Electronic data processing -- Quality control; Management; Electronic books; Electronic books